Implementasi Pojok Baca Sebagai Sarana Menumbuhkan Minat Baca di Miss Proto 02 Kedungwuni Pekalongan - Shofiani, Rissa; Afrizal, M (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
This study aims to describe the reading corner program at MISS Proto 02 Kedungwuni Pekalongan. The type of research used is field research while the approach used is a qualitative approach. The data sources used came from primary and secondary data. While the method of collection through observation, interviews, and documentation. This research uses descriptive analysis. The results showed that the implementation of the reading corner of MISS Proto 02 Kedungwuni Pekalongan includes various aspects, including planning, namely forming a student reading corner team and appointing a mentor. Then, implementation, namely during Indonesian language lessons and during the second break. Furthermore, evaluation, namely evaluation through the supervising teacher and evaluation based on student records.